Sporadic ALS hiPSC-derived motor neurons show axonal defects linked to altered axon guidance pathways - Lisha Ye; Katarina Stoklund Dittlau; Adria Sicart; Rekin'’s Janky; Philip Van Damme; Ludo Van Den Bosch (Neurobiology of Disease)
Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disorder characterized by the selective and progressive loss of motor neurons, leading to gradual paralysis and death within 2 to 5 years after diagnosis. The exact underlying pathogenic mechanism(s) remain elusive. This is particularly the case for sporadic ALS (sALS), representing 90 % of cases, as modelling a sporadic disease is extremely difficult. We used human induced pluripotent stem cell (hiPSC)-derived motor neurons from sALS patients to investigate early disease mechanisms. The earliest phenotype that we observed were profound axonal defects including impaired axonal transport, defective axonal outgrowth and a reduced formation of neuromuscular junctions. Transcriptomic profiling revealed significant dysregulation in axon guidance pathways, with upregulation of specific axonal regeneration-inhibiting genes, such as EphA4 and DCC in sALS motor neurons. Our findings suggest that dysregulation of axon guidance pathways contributes to axonal defects and that this could play a crucial role in the pathogenesis of sALS.